The digital transformation of the construction industry: a review - Daniela Vararean-Cochisa; Emil-Lucian Crisan (IIM Ranchi Journal of Management Studies)
Purpose – Although the recent increased efforts to implement digital transformation (DT), the construction sector field lags behind other sectors, and the academic research on the DT process remains rather fragmented. This study is an integrative review of the construction related literature concerning the context, interventions and outcomes of the DT process. Design/methodology/approach – We have reviewed 15 cases presenting the DT process of construction companies, by employing the context-intervention-mechanism-output (CIMO) framework. Findings – Regarding the context (C), the major drivers of DT are top management support, organizational culture pro DT and customer requirements. Concerning the intervention (I), BIM technology dominates construction firms' approaches to DT, followed by cloud computing and Internet of Things (IoT). The outcomes (O) of DT include direct and indirect benefits related to accurate cost calculations, cost reduction, improved work efficiency, high quality, as there are more complex results related to new business models and increased long-term competitiveness. DT in this field can be described considering three mechanisms (M), similar to a maturity model: traditional DT, niche DT and advanced DT. Originality/value – This review contributes to the literature by integrating existing studies on the context, interventions and outcomes of the DT process of the construction industry.